Is a Quantum Biosensing Revolution Approaching? Perspectives in NV‐Assisted Current and Thermal Biosensing in Living Cells. Issue 12 (27th September 2020) - Petrini, Giulia; Moreva, Ekaterina; Bernardi, Ettore; Traina, Paolo; Tomagra, Giulia; Carabelli, Valentina; Degiovanni, Ivo Pietro; Genovese, Marco
Abstract: Understanding the human brain is one of the most significant challenges of the 21st century. As theoretical studies continue to improve the description of the complex mechanisms that regulate biological processes, in parallel numerous experiments are conducted to enrich or verify these theoretical predictions also with the aim of extrapolating more accurate models. In the fields of magnetometry and thermometry, among the various sensors proposed for biological application, nitrogen‐vacancy (NV) centers are emerging as a promising solution due to their perfect biocompatibility and the possibility of being positioned in close proximity to the cell membrane, thus allowing a nanometric spatial resolution down to the nano‐scale. Still many issues must be overcome to obtain either a sensitivity capable of revealing the very weak electromagnetic fields generated by neurons (or other excitable cells) during their firing activity or a spatial resolution sufficient to measure intracellular thermal gradient due to biological processes. However, over the last few years, significant improvements have been achieved in this direction, thanks to the use of innovative techniques. In this review, the new results regarding the application of NV centers will be analyzed and the main challenges that must be afforded for leading to practical applications will be discussed. Abstract : Among the various sensors proposed for biological application, nitrogen‐vacancy (NV) centers are emerging due to their perfect biocompatibility and for the possibility of being few nanometers from the cell membrane. This review summarizes the most recent results on NV‐centers‐based biosensors and the main challenges to detect the weak electromagnetic fields generated by neurons or other excitable cells.